Effect of activated carbon in PSF-PEI-Ag symmetric membrane - Khairul Anwar, Mohamad Said; Genevieve Gadung, George; Nurul Ain, Mohamed Alipah; Nor Zakirah, Ismail; Ramizah Liyana, Jama'In (Publisher: EDP Sciences, 2016)
Polysulfone (Psf) composite membrane consist of activated carbon, polyethyleneimine and silver nitrate was prepared by phase inversion. The activated carbon (AC) act as adsorbent to adsorb heavy metal present in synthetic waste water while polysulfone membrane act as support. Phase inversion was carried out on different composition of activated carbon from 0 to 0.9% while other component are remain constant. The surface morphology of composite membrane was characterized by scanning electron microscopy (SEM) while heavy metal absorption was quantified by atomic absorption spectrometer (AAS). The SEM image show symmetric membrane matrix with sponge structure. The composite membrane with 0.9wt% AC has the highest water flux as well as removal of heavy metal (chromium, lead, silver and cadmium) compare to composite membrane with 0.3wt% AC and 0.5wt% AC. The percentage of heavy metal reduction by composite membrane 0.9wt% AC was 35% cadmium, 19% chromium, 16% silver and 2% lead. The result indicated that the introduction of 0.9wt% AC indeed plays an important role towards enhancing the adsorption of heavy metal in water.